ROHINGYA COMMUNITY IN KELANTAN: NATIONAL SECURITY CONCERNS AND LOCAL PERCEPTIONS - Zakaria, Hairunnisa (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
The presence of the Rohingya ethnic community in local settlements, particularly in the eastern coastal states, has elicited a range of apprehensions among the local populace. Kampung Peringat, Melor and Kota Bharu are among the primary locations for the settlement of the Rohingya ethnic community in Kelantan. Initially consisting of just a few individuals, the Rohingya population has increased significantly, now numbering in the thousands as illegal immigrants in the region. This research uses a qualitative approach, employing data gathered from both primary and secondary sources. Data is collected through interviews and observations within relevant domains. Secondary data is drawn from empirical sources, including dissertations, academic journals, and online databases. This research encompasses three primary objectives: 1) to examine the implications of the influx of the Rohingya ethnic community in Kelantan; 2) to assess the management and security protocols in response to the arrival of Rohingya ethnic refugees in Kelantan; and 3) to evaluate the effectiveness of governmental policies aimed at managing and regulating the presence of the Rohingya ethnic community in Kelantan. The findings of this study indicate that 1) the presence of this community has given rise to a range of social, economic, and security challenges, such as increased competition in the job market, greater use of public facilities, and negative perceptions regarding national security; 2) the management and security measures necessitated by the influx of Rohingya refugees in Kelantan have not been effectively implemented; and 3) the current governmental strategies for managing Rohingya refugees are viewed as inadequate, with lax enforcement heightening the concerns of the local populace. This study advocates for the government to implement more effective actions in the management of Rohingya refugees, thus safeguarding the well-being and security of Malaysians.